علاقة التخطيط الاستراتيجي بفاعلية إدارة الأزمات والمخاطر في المنظمات الصحية العراقية - داخل، مؤيد عطا; جماعة، عبدالله أمين محمود; أبو زيد، حمادة فوزي ثابت (جامعة بنها - كلية التجارة, 2022)
يهدف البحث الحالي إلى توصيف وتقييم للممارسات الفعلية لسياسات التخطيط الاستراتيجي في المؤسسات الصحية العراقية وقياس مدى الارتباط بين التخطيط الاستراتيجي وإدارة الأزمات في المؤسسات الصحية العراقية، وتحديد نموذج مقترح للعلاقة بين التخطيط الاستراتيجي وإدارة الأزمات في المؤسسات الصحة العراقية، وتقديم وصياغة مجموعة من التوصيات التي تعمل على تحسين الممارسات الفعلية لسياسات بالإضافة إلى التخطيط الاستراتيجي، للحد من الآثار السلبية للأزمات التي قد تواجه المؤسسات الصحية العراقية في المستقبل. وقام الباحث بتحديد مجتمع الدراسة المتمثل في العاملين في بعض المستشفيات العراقية الحكومية الزهراء) التعليمي، الكرامة التعليمي، اليرموك التعليمي)، وكذلك العاملين في بعض المستشفيات الخاصة الهلال الأحمر، الجادرية الأهلي، الراهبات الأهلي في الأقسام التالية: قسم الجراحة قسم الباطنة قسم المختبر، قسم الصيدلية قسم الأشعة، قسم الطوارئ قسم الكسور، للوظائف التالية: مديري العموم، معاون المدير العام، رئيس وحدة، معاون رئيس وحدة، رئيس قسم معاون رئيس قسم، وعددهم نحو (١٣٧٦) مفردة، وتوصلت الدراسة إلى مشاركة كافة العاملين في صياغة رؤية ورسالة المؤسسة، وتحديد واضح لرؤية ورسالة المؤسسة بما يتوافق مع أسباب وجودها في البيئة، والقيام بعمليات تحديد الأهداف الاستراتيجية بشكل يحقق خصائص الأهداف الذكية. The current research aims to characterize and evaluate the actual practices of strategic planning policies in Iraqi health institutions, measure the extent of the link between strategic planning and crisis management in Iraqi health institutions, identify a proposed model for the relationship between strategic planning and crisis management in Iraqi health institutions, and present and formulate a set of recommendations that work To improve the actual practices of policies in addition to strategic planning, to reduce the negative effects of crises that may face Iraqi health institutions in the future. The researcher identified the study population represented by workers in some Iraqi governmental hospitals (Al-Zahra Educational, Al- Karama Educational, Al-Yarmouk Educational), as well as workers in some private hospitals (Red Crescent, Al-Jadriya Al-Ahly, Al-Ahly Nuns) in the following departments: Surgery Department, Internal Medicine Department, Laboratory department, pharmacy department, radiology department, emergency department, fracture department, for the following positions: general managers, assistant general manager, unit head, assistant unit head, department head, assistant department head, and their number is about (1376), and the study found the participation of All workers in the formulation of the vision and mission of the institution, and a clear definition of the vision and mission of the institution in line with the reasons for its presence in the environment, and carry out the processes of setting strategic goals in a way that achieves the characteristics of smart goals.
Keywords: التخطيط الاستراتيجي -- إدارة الأزمات -- المؤسسات الصحية -- العراق